Public Opinion on Cashless Transaction - JOSHI, DR. VINAY (The journal of contemporary issues in business and government, 2021)
After demonetization initiatives, most of the people in India started electronic payments for their transactions. Everyone from the small merchant to the neighboring vegetable vendor is embracing digital payment solutions. Slowly India is moving from cash to cashless economy. A cashless economy is one in which all the transactions are done using cards or digital means (using smartphones). The circulation of physical currency is minimal in the cashless economy this reduces the usage of paper which decreases the cutting of the paper tree. There are numerous benefits of Cashless transactions. The increased use of credit cards will reduce the amount of cash that people have to carry which reduces the risk of misshaping and the cost associated with that. In this paper, an attempt is made to examine the Public perception in India towards cashless transactions and the attempt is also made to identify the challenges faced by them during their transactions.